Case Report: A Case of Hailey–Hailey Disease Mimicking Condyloma Acuminatum and a Novel Splice-Site Mutation of ATP2C1 Gene - Dai, Yuwei; Yu, Lingling; Wang, Yu; Gao, Min; Wang, Peiguang (Frontiers in Genetics, 2021)
Hailey–Hailey disease (HHD) is a rare autosomal-dominant blistering disorder characterized by recurrent vesicular and erosive lesions at intertriginous sites. We described a 24-year-old male who presented with multiple bright red verrucous papules in his mons pubis, bilateral groins, scrotum, perineum, and crissum, clinically resembling condyloma acuminatum. The histopathology showed extensive acantholysis with the characteristic appearance of a dilapidated brick-wall. The mutation analysis revealed a novel splice-site mutation in the ATP2C1 gene. The patient was definitely diagnosed with HHD. The antibacterial treatments resulted in a dramatic improvement. Our findings help to broaden the understanding of clinical manifestations of HHD and improve the clinical diagnosis and treatment of this disease.